Pola Pendidikan Islam Versi Ibnu Sina - Safaruddin, Safaruddin; Roza, Ellya (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The aim of this research is to analyze the Ibn Sina Version of Islamic Education Patterns. This type of research is a library study. Data collection with documentation. Data analysis with SLR. The research results obtained are Ibn Sina's version of the Islamic education pattern emphasizes the integration of science and spirituality in the learning process. According to him, education must strengthen the mind and heart, as well as develop intellectual and moral skills. Ibn Sina emphasized the importance of holistic learning, where students not only master academic knowledge, but also gain a deep understanding of Islamic values and practical skills to apply them in everyday life.